A kind of amphiphilic polymer of polyaspartic acid grafted with oleylamine and its application

The existing biomass of magnetic resonance contrast agents and photosensitizers are solved by coating superparamagnetic iron oxide nanocrystals and indylcyanogenic greens using polyaspartic acid-grafted oysteramine. Safety and stability issues, achieving dual-mode magnetic resonance/fluorescence imaging and efficient photothermal therapy.

CN116217944BActive Publication Date: 2025-02-11NORTH SICHUAN MEDICAL COLLEGE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310244750.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-14
Publication Date
2025-02-11
Estimated Expiration
2043-03-14

AI Technical Summary

Technical Problem

Existing magnetic resonance contrast agents and photosensitizers have biosafety and stability problems, especially nephrogenic systemic fibrosis diseases and manganese poisoning caused by gadolinium agents, instability and short half-life of indolecyanochloride.

Method used

An amphiphilic polymer of polyaspartic acid grafted oleamine coated with superparamagnetic iron oxide nanocrystals and indylcyanine green to form nanomicromicroscopy for preparation of magnetic resonance/fluorescence dual-modal imaging nanomicroscopy .

Benefits of technology

It has achieved a long circulation time in the blood and good longitudinal relaxation effect under clinical magnetic field. It is also used as a photosensitive agent guided by multimodal imaging, which can play the therapeutic role of drugs more accurately and efficiently, overcoming traditional imaging. Biosafety and stability issues of agents and photosensitizers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004125543850000031
    Figure BDA0004125543850000031
  • Figure BDA0004125543850000041
    Figure BDA0004125543850000041
Patent Text Reader

Abstract

The invention discloses an amphiphilic polymer of polyaspartic acid grafted with oleylamine and an application thereof. The polymer is a polyaspartic acid-dopamine / oleylamine / polyethylene glycol grafted copolymer, and the copolymer is used for encapsulating superparamagnetic iron oxide nanocrystals and indocyanine green, and for use in a diagnosis-treatment integrated nanomedicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical diagnosis, and in particular relates to an amphiphilic polymer of polyaspartic acid grafted with oleylamine and application thereof. Background Art

[0002] At present, safe and efficient delivery of drugs to target sites is the core issue of drug development for diagnosis and treatment. Drug delivery based on nanoparticles has the potential to solve this problem. By loading anticancer drugs into nanoparticles, the good pharmacokinetics and adjustable biodistribution characteristics of nanoparticles are used to improve the aggregation of drugs at the lesion site, thereby improving diagnostic efficiency or therapeutic effect. Among the numerous nano drug delivery systems, nano micelles have attracted widespread attention in the field of nanomedicine due to their low cost, good biocompatibility, and simple preparation. The outer layer of nano micelles has hydrophilic and hydrophobic groups, and these molecules are determined by the orientation of the environment to assemble into ordinary nano micelles (in polar solvents, the hydrophobic groups are located in the core) or reverse nano micelles (in non-polar solvents, the hydrophobic groups are facing the surface). This characteristic makes it easy for different types of drugs to be loaded into nano micelles. The outer shell of the micelle acts as a protective layer by reducing the direct contact between the drug and the internal environment, thereby improving the utilization rate of the drug and reducing the side effects of the drug on other normal tissues and organs.

[0003] With the continuous development of drug delivery systems and the pursuit of precision medicine, drugs that integrate diagnosis and treatment have become the main development direction. Combining diagnosis with treatment not only makes the treatment process more accurate and efficient, but also can evaluate its therapeutic effect to a certain extent. Among the commonly used clinical diagnostic methods, magnetic resonance imaging is currently the most widely used clinical diagnostic method due to its non-invasive, safe, non-ionizing radiation, multi-parameter, multi-plane imaging characteristics and excellent image quality to provide anatomical and functional information. Based on the importance of MRI and the role of contrast agents in enhancing imaging sensitivity, many researchers have tried to use different techniques to improve the performance of contrast agents in order to continuously obtain better image contrast. Generally, the contrast agents commonly used in clinical practice are mainly gadolinium agents, but in recent years, it has been found that gadolinium agents can cause nephrogenic systemic fibrosis and brain residual risks. The large-scale use of gadolinium agents has caused people to worry about their long-term safety, which has made manganese-based and iron-based contrast agents with higher biosafety the focus of attention, but Mn 2+ The blood circulation time of the complex is very short, and high doses of Mn 2+It can accumulate in the brain, leading to manganese poisoning, manifested as changes in central nervous system activity, leading to cognitive, mental and motor abnormalities. Therefore, iron-based contrast agents have become ideal candidates for current magnetic resonance contrast agents. Among them, superparamagnetic iron oxide nanoparticles (SPIO) have attracted much attention in the biomedical field because of their long blood half-life, low toxicity and flexible surface chemistry, which can effectively shorten the transverse relaxation time. SPIO has also been shown to be effectively cleared from the body and has a natural degradation mechanism, being metabolized to hemoglobin in the body. In addition, in order to improve the biocompatibility of SPIO, polysaccharides such as dextran and chitosan, polyethylene glycol (PEG), polypyrrole (PPy), and polylactic acid (PLA) are usually used to encapsulate and modify it to reduce its toxicity and increase its circulation time in the body.

[0004] Indocyanine green (ICG) has been shown to have good photothermal conversion effects as a clinical diagnostic drug, but ICG is a small molecule fluorescent dye that is easy to self-quench, has low fluorescence quantum yield in aqueous solution, poor thermal stability and other disadvantages. Secondly, ICG is easy to non-specifically bind to albumin, globulin and lipoprotein in plasma, and is quickly cleared from the circulatory system through the action of the liver, resulting in a short initial half-life. Therefore, there are still challenges in the use of ICG for photothermal therapy. CN115089731A discloses a nano drug delivery system for synergistic chemotherapy and photothermal therapy, and its preparation method and application, including (1) connecting single-walled nanotubes and photothermal converters through disulfide bonds to obtain sensitive nano carriers; (2) using HA-DMPE to modify the sensitive nano carrier and load the drug to obtain a nano drug delivery system for synergistic chemotherapy and photothermal therapy. The preparation method of this system is simple, and the obtained HA-DMPE / SWCNTs-PEG-SS-ICG sample has uniform particle size distribution and stable physical and chemical properties. The carrier has high encapsulation rate and loading capacity for ICG and DOX, and can achieve responsive drug release in a simulated tumor microenvironment. At the same time, it has good photothermal conversion performance, which can increase the uptake of ICG and DOX by MCF-7 cells, and achieve effective synergistic anti-tumor effects of chemotherapy and PTT. However, the large particle size of the nanodrug (300-350nm) is not conducive to the nanodrug entering the tumor site to exert a therapeutic effect, and the photothermal converter (ICG) and the single-walled nanotubes are linked by disulfide bonds, which does not improve its instability. Summary of the invention

[0005] The purpose of the present invention is to provide an amphiphilic polymer of polyaspartic acid grafted with oleylamine and its application. The amphiphilic polymer is composed of polyaspartic acid-dopamine / oleylamine / polyethylene glycol amphiphilic grafted polymer and the use of the polymer in preparing magnetic resonance contrast agents and photosensitizers.

[0006] To achieve the purpose of the present invention, the following embodiments are provided.

[0007] In one embodiment, the amphiphilic polymer of polyaspartic acid grafted with oleylamine of the present invention is as shown in Formula I, and the amphiphilic polymer is obtained by grafting a hydrophobic group oleylamine and a hydrophilic group polyethylene glycol, as well as dopamine, onto a polyaspartic acid backbone.

[0008]

[0009] In the formula,

[0010] R is hydrogen or methyl,

[0011] x is 1 to 500, and y, z and n are independently 1 to 500.

[0012] In another embodiment, the present invention also provides a nanomicelle of superparamagnetic iron oxide nanocrystals coated with polyaspartic acid, comprising a polymer shown in formula I, superparamagnetic iron oxide nanocrystals and indocyanine green, characterized in that the nanomicelle is obtained by coating the superparamagnetic iron oxide nanocrystals and indocyanine green with the amphiphilic polymer of polyaspartic acid grafted with oleylamine shown in formula I.

[0013] In another embodiment, the present invention provides a method for preparing an amphiphilic polymer of polyaspartic acid grafted with oleylamine, comprising the following steps:

[0014] 1) dissolving polysuccinimide and amino-terminated polyethylene glycol in dimethyl sulfoxide, and reacting at 80° C. for 48 hours under nitrogen protection;

[0015] 2) Under nitrogen protection, oleylamine was added to the reaction solution in the previous step, and the mixture was reacted at 80°C for 24 hours. Dopamine hydrochloride dissolved in dimethyl sulfoxide and triethylamine was then added and reacted at 80°C. Then, sodium hydroxide solution was added and the reaction was continued;

[0016] 3) After the reaction is completed, the pH is adjusted to 6 with hydrochloric acid solution, the reaction solution is placed in a dialysis bag, and dialyzed in an aqueous solution for 24 hours, the solution in the dialysis bag is collected, and freeze-dried to obtain a polymer represented by formula I.

[0017] Furthermore, the present invention provides a method for preparing nanomicelles of polyaspartic acid-coated superparamagnetic nanoparticles, comprising the following steps:

[0018] 1) dissolving the polymer of formula (I) in chloroform to obtain a polymer solution;

[0019] 2) dispersing superparamagnetic iron oxide nanocrystals in n-hexane, removing the n-hexane and dissolving with chloroform to obtain a superparamagnetic iron oxide nanocrystal solution;

[0020] 3) Dissolve indocyanine green in a mixed solvent of methanol and chloroform to obtain an indocyanine green solution

[0021] 4) mixing the three solutions of steps 1) to 3) and slowly dropping them into ultrapure water under ultrasound to form a nanomicelle solution;

[0022] 5) The nanomicelle solution is evaporated to remove the organic solvent, the solution is placed in a dialysis bag, and dialyzed in ultrapure water for 24 hours, the solution in the dialysis bag is collected, and filtered to remove large particles to obtain nanomicelles.

[0023] Preferably, in the preparation method of the present invention, the superparamagnetic iron oxide nanocrystals in step 1) are SPIO@OA.

[0024] The present invention also aims to provide the use of the nanomicelles of the polyaspartic acid coated superparamagnetic iron oxide nanocrystals of the present invention in the manufacture of photosensitizers guided by magnetic resonance / fluorescence imaging.

[0025] The present invention also aims to provide the use of the amphiphilic polymer of polyaspartic acid grafted with oleylamine for preparing magnetic resonance and fluorescence dual-modal imaging nano-micelles.

[0026] In a specific embodiment, the amphiphilic polymer of polyaspartic acid grafted with oleylamine of the present invention has a polyaspartic acid-dopamine / oleylamine / polyethylene glycol amphiphilic grafted polymer as shown in formula I (also referred to herein as "polyaspartic acid-dopamine / oleylamine / polyethylene glycol polymer" or polymer shown in formula I), wherein the amphiphilic polymer is composed of a polyaspartic acid backbone grafted with hydrophobic oleylamine as a hydrophobic group, grafted with polyethylene glycol as a hydrophilic group, and dopamine,

[0027]

[0028] Wherein, R=-CH3, H; x is 1 to 500, and y, z and m are independently 1 to 500.

[0029] In another specific embodiment, a nano-micelle of a polyaspartic acid-coated superparamagnetic iron oxide nanocrystal of the present invention is a nano-micelle of a superparamagnetic iron oxide nanocrystal and an indocyanine green-coated polymer represented by formula I, characterized in that the system is a spherical, single-coated nanoparticle under a transmission electron microscope, which includes the above-mentioned amphiphilic grafted polymer and the encapsulated indocyanine green and superparamagnetic iron oxide nanocrystal, see Figure 2 .

[0030] On the one hand, the present invention provides a method for preparing a polymer shown in formula I, comprising placing polysuccinimide and amino-terminated polyethylene glycol in a reaction bottle, adding dimethyl sulfoxide and stirring to dissolve, reacting at 80°C for 48 hours under nitrogen protection, adding oleylamine and continuing to react at 80°C for 24 hours under nitrogen environment, finally dissolving dopamine hydrochloride with dimethyl sulfoxide and triethylamine, adding them to the reaction bottle at 80°C under nitrogen protection, reacting, adding sodium hydroxide solution, continuing the reaction, and after the reaction, adjusting the pH to 6 with hydrochloric acid solution, placing the reaction solution in a dialysis bag, dialyzing it in an aqueous solution for 24 hours, collecting the solution in the dialysis bag, and freeze-drying it to obtain a product.

[0031] On the other hand, the present invention provides a method for preparing nano-micelles of superparamagnetic iron oxide nano-crystals coated with polyaspartic acid, comprising dissolving a polyaspartic acid-dopamine / oleylamine / polyethylene glycol amphiphilic graft polymer of formula I in chloroform to form a polymer solution; dispersing organic phase superparamagnetic iron oxide nano-crystals in n-hexane, removing the n-hexane and dispersing the organic phase in chloroform to form a superparamagnetic iron oxide nano-crystal solution; dissolving indocyanine green in a mixed solvent of methanol and chloroform to form an indocyanine green solution, mixing the above three solutions, slowly dropping them into ultrapure water under ultrasound to self-assemble to form a nano-micelle solution, removing the organic solvent therein by rotary evaporation, placing the solution in a dialysis bag, dialyzing it in ultrapure water for 24 hours to remove indocyanine green molecules that are not coated, and finally collecting the solution in the dialysis bag and filtering it to remove large particles, thereby obtaining an aqueous solution of nano-micelles coating superparamagnetic iron oxide nano-crystals and indocyanine green. The superparamagnetic iron oxide nanocrystals are superparamagnetic iron oxide nanoparticles coated with oleic acid, namely, SPIO@OA (which is the abbreviation of superparamagnetic iron oxide nanoparticles coated with oleic acid).

[0032] The nano-micelles of ferroferric oxide nanoparticles and indocyanine green coated with the polymer of formula I of the present invention are characterized in that the nano-micelles have a long circulation time in the blood.

[0033] The polymer-encapsulated superparamagnetic iron oxide nanocrystals and indocyanine green nanomicelles of the present invention have good longitudinal relaxation performance (0.5T: 63.12mM -1 s -1 ; 1.5T: 70.95mM -1 s -1 ; 3.0T: 84.5mM -1 s -1), can be used as an excellent magnetic resonance T2 contrast agent. When the polymer encapsulates the iron oxide nanoparticles, it is a single encapsulation (one iron oxide nanocrystal is encapsulated in one nanoparticle), which has a smaller hydrodynamic particle size than the multi-encapsulated iron oxide nanoclusters, and is easy to enter the tumor site to exert its effect. In addition, the nanomicelles encapsulating superparamagnetic iron oxide nanocrystals and indocyanine green of the present invention can be used as both a T2 contrast agent and a fluorescent dye and a photosensitizer. It is a multimodal imaging-guided photosensitizer, which can more accurately and efficiently exert the therapeutic effect of the drug compared to traditional photothermal therapeutic agents. The multivalently grafted dopamine in the amphiphilic polymer can not only synergize with ICG to exert photothermal and photodynamic effects, but also stably chelate with ferroferric oxide nanoparticles and cross-link molecules to increase the stability of the nanomicelles. In addition, encapsulating ICG inside the micelles blocks its contact with the outside world, increases the stability of ICG in the body, and is more suitable for photothermal therapy. The π-π stacking of ICG molecules inside the micelles causes a red shift in its characteristic absorption peak, making it more suitable as a photosensitizer for 808nm laser excitation. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The polyaspartic acid-dopamine / oleylamine / polyethylene glycol graft copolymer of Example 1 1 H NMR spectrum;

[0035] Figure 2 The polymer-coated ferroferric oxide nanoparticles and indole cyanine green ultraviolet-visible light absorption spectra of the present invention;

[0036] Figure 3 Schematic diagram of nanomicelles of superparamagnetic iron oxide nanocrystals and indocyanine green coated with a polymer represented by formula I of the present invention;

[0037] Figure 4 The T1 and T2 relaxation efficiencies of the nanomicelles formed by encapsulating superparamagnetic iron oxide nanocrystals and indocyanine green with the polyaspartic acid-dopamine / oleylamine / polyethylene glycol grafted polymer of Example 2 at 3.0 T;

[0038] Figure 5 The T2-weighted imaging effect of nanomicelles formed by polyaspartic acid-dopamine / oleylamine / polyethylene glycol grafted polymer encapsulating superparamagnetic iron oxide nanocrystals and indocyanine green in Example 2 at different concentrations of aqueous solution at 3.0T;

[0039] Figure 6 The dynamic light scattering particle size distribution diagram of nanomicelles formed by encapsulating superparamagnetic iron oxide nanocrystals and indocyanine green by polyaspartic acid-dopamine / oleylamine / polyethylene glycol grafted polymer of Example 2;

[0040] Figure 7The characteristic absorption peak value changes of the nanomicelles formed by the polyaspartic acid-dopamine / oleylamine / polyethylene glycol grafted polymer encapsulating the superparamagnetic iron oxide nanocrystals and indocyanine green in Example 2 and placed at different temperatures for different times;

[0041] Figure 8 The temperature changes of nanomicelles with different concentrations when irradiated with 808nm laser for 10min continuously;

[0042] Fig. 9 The graph is a graph showing the consumption of active oxygen probe DPBF by active oxygen generated by nanomicelle solution after 808nm laser irradiation for different time periods by detecting the change of characteristic absorption peak of DPBF by UV spectrophotometer;

[0043] Fig.10 Cell survival rate of melanoma cells under co-culture with different concentrations of nanoparticles, 808nm laser irradiation and without irradiation. DETAILED DESCRIPTION

[0044] The following examples are merely representative and are used to further understand the spirit of the present invention, but are not intended to limit the scope of the present invention.

[0045] Example 1 Preparation of polyaspartic acid-dopamine / oleylamine / polyethylene glycol graft copolymer

[0046] The reaction mechanism is as follows:

[0047]

[0048] Preparation method:

[0049] Accurately weigh 0.5 g of polysuccinimide (PSI, weight average molecular weight 7000 g / mol) and 1 g of amino-terminated methoxy polyethylene glycol (CH3-PEG-NH2, molecular weight 2000 g / mol) in a reaction bottle, add 4 ml of dimethyl sulfoxide (DMSO) and stir to dissolve, react at 80 °C under nitrogen protection for 48 hours, and then add 161 μL of oleylamine (C 18 H 37N, molecular weight 267g / mol) continue to react at 80°C under nitrogen environment for 24 hours, then accurately weigh 1g of dopamine hydrochloride, dissolve it with 0.8ml of triethylamine, and add it to the reaction bottle under nitrogen protection. Place the reaction bottle in an 80°C oil bath to react for 24 hours, and adjust the oil bath temperature to 60°C. Accurately weigh 0.2g of sodium hydroxide, dissolve it with 3ml of water and add it to the reaction bottle, and continue to react for 24 hours. After the reaction is completed, adjust the pH to 6 with 1M hydrochloric acid solution. The reaction solution is placed in a dialysis bag with a molecular weight cutoff of 3500Da and dialyzed in an aqueous solution for 24 hours. Collect the solution in the dialysis bag and lyophilize to obtain the target product. The reaction product was characterized by hydrogen nuclear magnetic resonance, such as Figure 1 shown.

[0050] Example 2 Preparation of Superparamagnetic Iron Oxide Nanocrystals and Indocyanine Green Nanomicelles Encapsulated by Polyaspartic Acid-Dopamine / Oleylamine / Polyethylene Glycol Grafted Polymer

[0051] Preparation process:

[0052] Accurately weigh 9 mg of polyaspartic acid-dopamine / oleylamine / polyethylene glycol grafted polymer in an EP tube, add 200 μL of chloroform to dissolve for later use; accurately weigh 1 mg of indocyanine green in an EP tube, add 200 μL of chloroform and methanol mixed solution (chloroform to methanol ratio is 3:1) to dissolve for later use; take 138 μL of oleic acid-coated superparamagnetic iron oxide nanocrystals (6 nm SPIO@OA, Fe concentration is 0.0145 mg / mL) dispersed in n-hexane in an EP tube, blow dry the organic solvent with nitrogen and redisperse in chloroform for later use, mix the above three different solutions, slowly add them dropwise into 10 ml of ultrapure water under ultrasound to self-assemble into nanomicelles, then remove the organic solvent by rotary evaporation, and place the solution in a dialysis bag with a molecular weight cutoff of 10000 Da. overtake The solution was dialyzed in pure water for 24 hours to remove the unencapsulated ICG molecules. Finally, the solution in the dialysis bag was collected and filtered with a filter (pore size of 0.22 μm) to remove large particles, thereby obtaining an aqueous solution of nanomicelles encapsulating superparamagnetic iron oxide nanocrystals and ICG.

[0053] Detection of the properties of the nanomicelles prepared in Example 2

[0054] The characteristic absorption peak changes of ICG before and after being encapsulated by the amphiphilic graft polymer described in Example 1 were measured by UV-visible spectrophotometer. It was shown that after encapsulation, the characteristic absorption peak of ICG molecules was red-shifted due to the π-π stacking, and there was stronger absorption at 808nm. The iron concentration in the solution was determined by atomic absorption, and the particle size, particle size distribution and Zeta potential of the nanoparticles were determined by dynamic light scattering. The results are shown in Figure 2, showing that after encapsulation, the characteristic absorption peak of ICG molecules red-shifts due to the π-π stacking, with stronger absorption at 808 nm.

[0055] The shape and structure of the prepared nanomicelles are shown in Figure 3 .

[0056] The nanoparticle solution was prepared into solutions with different iron concentrations such as 0.04998, 0.114, 0.2034, 0.2997, and 0.4066 mM, respectively. The T1 and T2 relaxation times of each sample were measured using a 0.5T, 1.49T magnetic resonance relaxation efficiency instrument, and a 3.0T magnetic resonance scanner, respectively. The T1 and T2 relaxation efficiencies (r1 and r2) were calculated, respectively. The results are shown in Figure 4 .

[0057] The T2-weighted imaging effect of different concentrations of aqueous solutions of nano-micelle particles (iron concentration ranges from 0.05 to 0.4 mM) at 3.0 T is shown in the following figure. Figure 5 , showing that the nanoparticles have a good T2 enhancement effect (reducing MRI signals in T2-weighted imaging) in both clinical use and 3.0T magnetic resonance imaging.

[0058] Particle size distribution detection: Dynamic light scattering particle size distribution of nanomicelles was detected. The average particle size was 23.43±1.47nm and the Zeta potential was -12mV±0.55mV. The results are shown in Figure 6 Compared with nano drugs with larger particle sizes, the nano size of the present invention is more conducive to the drug entering the tumor site.

[0059] The nanomicelle solution and free ICG solution were stored at different temperatures in the dark, and the changes in their characteristic peak absorption values ​​were monitored at different times using a UV-visible spectrophotometer. The results are as follows: Figure 7 After ICG was encapsulated in the micelles, its stability was improved to a certain extent. Laser continuous irradiation of nanomicelles: The temperature changes of nanomicelles with different concentrations were continuously irradiated with 808nm laser for 10 minutes. The results are shown in Figure 8 The nanomicelles irradiated with 808nm laser for different time periods were detected by UV spectrophotometer to detect the changes in the characteristic absorption peak of DPBF to reflect the consumption of the active oxygen probe DPBF by the active oxygen generated by the nanomicelle solution. Fig. 9 , showing that the synergistic effect of ICG and dopamine in the nanomicelles enables the nanomicelles to exhibit good photothermal and photodynamic conversion capabilities in vitro.

[0060] The polymers of the present invention are all grafted with materials with good biocompatibility, and the outer layer of the micelles is modified with polyethylene glycol, so that the nano-micelles formed by the polymers have the characteristics of low toxicity at the cell level when there is no laser irradiation of a suitable wavelength. However, after irradiation with an 808nm laser, the nano-micelles show a significant killing effect on cells, such as Fig.10 The results proved that the nanomicelles have low toxicity and strong killing ability at the cellular level and can be used in the study of in vivo photothermal / photodynamic therapy.

[0061] The nano micelles of the present invention can be used for photosensitizers guided by magnetic resonance and fluorescence dual-modality imaging, and have the following advantages over traditional photosensitizers: 1. magnetic resonance and fluorescence dual-modality imaging guidance improves the accuracy and efficacy of photothermal and photodynamic therapy; 2. the amphiphilic polymer physical encapsulation method constructed by grafting with good biocompatible materials is used to carry superparamagnetic iron oxide nanocrystals and indocyanine green, overcomes the shortcomings of traditional gadolinium agents as magnetic resonance contrast agents to produce nephrogenic systemic fibrosis and the risk of gadolinium residue in the body, and improves the shortcomings of indocyanine green itself being unstable. 3. The indocyanine green molecules inside the micelles undergo π-π stacking to red-shift their characteristic absorption peaks, and the absorption at 808nm is stronger, and indocyanine green and dopamine in the amphiphilic polymer cooperate with each other, so that the nano micelles have better photothermal and photodynamic conversion capabilities.

[0062] The polymer in the prior art CN111607094A forms a nanocomposite by chemically bonding with metal ions only by virtue of the catechol structure of the dopamine molecule, so it only chelates with hydrophilic metal ions. The amphiphilic polymer of polyaspartic acid grafted with oleylamine of the present invention, due to the grafting of oleylamine, becomes an amphiphilic polymer, and can form ordinary micelles to encapsulate hydrophobic drugs, or form reverse micelles to encapsulate hydrophilic drugs, and has a wider range of uses. In addition, the dopamine in the polymer is cross-linked with each other, so that the nano micelles formed by the polymer are more stable than ordinary micelles.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nanomicelle of polyaspartic acid-coated superparamagnetic nanoparticles, comprising a polymer represented by formula I, superparamagnetic iron oxide nanocrystals and indocyanine green, characterized in that: Nanomicelles are obtained by coating superparamagnetic iron oxide nanocrystals and indocyanine green with a polymer shown in formula I. I In the formula, R is hydrogen or methyl, x is 1 to 500, y, z and n are all 1 to 500 independently, The method for preparing the nanomicelles of polyaspartic acid-coated superparamagnetic nanoparticles comprises the following steps: 1) dissolving the polymer represented by formula I in chloroform to obtain a polymer solution; 2) dispersing superparamagnetic iron oxide nanocrystals in n-hexane, removing the n-hexane and dissolving with chloroform to obtain a superparamagnetic nanoparticle solution; 3) dissolving indocyanine green in a mixed solvent of methanol and chloroform to obtain an indocyanine green solution; 4) Mix the three solutions of steps 1) to 3) and slowly add them dropwise into ultrapure water under ultrasound to form a nanomicelle solution; 5) The nanomicelle solution is evaporated to remove the organic solvent, the solution is placed in a dialysis bag, and dialyzed in ultrapure water for 24 hours, the solution in the dialysis bag is collected, and filtered to remove large particles to obtain nanomicelles.

2. The nanomicelle according to claim 1, wherein the preparation method comprises step 2) wherein the superparamagnetic iron oxide nanocrystals are SPIO@OA.

3. The nanomicelle as claimed in claim 1, wherein the polymer shown in formula I is prepared by grafting a hydrophobic group oleylamine and a hydrophilic group polyethylene glycol onto a polyaspartic acid backbone, and dopamine.

4. The nanomicelle as claimed in claim 3, wherein the preparation of the polymer represented by formula I comprises the following steps: (1) dissolving polysuccinimide and amino-terminated polyethylene glycol in dimethyl sulfoxide and reacting under nitrogen protection; (2) After the above reaction is completed, under nitrogen protection, oleylamine is added to the reaction solution for reaction, then dopamine hydrochloride dissolved in dimethyl sulfoxide and triethylamine is added for reaction, and then sodium hydroxide solution is added to continue the reaction; (3) After the reaction is completed, the pH is adjusted to 6 with a hydrochloric acid solution, and the reaction solution is placed in a dialysis bag and dialyzed in an aqueous solution. After the dialysis is completed, the solution in the dialysis bag is collected and freeze-dried to obtain a polymer represented by Formula I.

5. The nanomicelle as claimed in claim 4, wherein in step (1), the weight (g) ratio of polysuccinimide, amino-terminated polyethylene glycol and dopamine hydrochloride is 0.5:1:

1.

6. The nanomicelle as claimed in claim 4, wherein the mass volume ratio of polysuccinimide to oleylamine in step (2) is 0.5 g:161 µL.

7. The nanomicelle according to claim 5 or 6, wherein the weight average molecular weight of the polysuccinimide is 7000 g / mol, and the molecular weight of the amino-terminated polyethylene glycol is 2000 g / mol.

8. The nanomicelle as claimed in claim 4, wherein the reaction temperature of step (1) is 80°C and the reaction time is 48 hours, and the reaction temperature of step (2) is 80°C and the oleylamine reaction time is 24 hours, and the dialysis time of step (3) is 24 hours.

9. Use of the nanomicelles of superparamagnetic iron oxide nanocrystals coated with polyaspartic acid according to claim 1 in the manufacture of photosensitizers guided by magnetic resonance and fluorescence dual-modality imaging.

Citation Information

Patent Citations

  • Nano-drug delivery system for synergistic chemotherapy and photothermal therapy as well as preparation method and application of nano-drug delivery system

    CN115089731A

  • Method for hydrophilization surface modification of hydrophobic nano-particles with oleylamine modified polysuccinimide

    CN105195736A

  • Polyaspartic acid-dopamine / polyethylene glycol polymer and application thereof in preparation of contrast agent

    CN111607094A